Living religions across transnational spaces: experiences of South Asian American Hindu and Muslim women. Issue 2 (3rd April 2021) - Kibria, Nazli; Purkayastha, Bandana; Narayan, Anjana; Khan, Koyel; Yousaf, Farhan Navid
ABSTRACT: This paper focuses on women of Indian, Bangladeshi and Pakistani origin in the US diaspora to examine how religious identities unfold within multi-layered transnational structures that range from political histories and events to active webs of family and community relationships that stretch across the diaspora. Our analysis draws on focus groups and interviews with highly educated Hindu and Muslim women in the US. For these women, approaches to religion were marked by multiple points of tension and negotiation, including the work of situating oneself within the intersecting power structures of the diaspora and country of origin, including a transnational sphere that is increasingly crafted through the reach of social media. These women's narratives show they are minorities in the US, and part of majorities in countries of origin, but, sometimes, outsiders to the local politics of religions. Focusing on these women allows us to reflect on the ways in which histories and contemporary events shape contemporary South Asia far beyond its geographic location.